The Routledge handbook of animal ethics - Fischer, Bob (Robert William) (New York, NY : Routledge, 2020)
"There isn't one conversation about animal ethics. Instead, there are several important ones that are scattered across many disciplines. This volume both surveys the field of animal ethics and draws professional philosophers, graduate students, and undergraduates more deeply into the discussions that are happening outside of philosophy departments. To that end, the volume contains more non-philosophers as philosophers, and it explicitly invites scholars from other fields-like animal science, ecology, economics, psychology, law, environmental science, and applied biology, among others-- to bring their own disciplinary resources to bear on matters that affect animals. The Routledge Handbook of Animal Ethics is comprised of 44 chapters, all appearing in print here for the first time, and organized into the following six sections: I. Thinking About Animals II. Animal Agriculture and Hunting III. Animal Research and Genetic Engineering IV. Companion Animals V. Wild Animals: Conservation, Management, and Ethics VI. Animal Activism The chapters are brief and they've been written in a way that's accessible to serious undergraduate students, regardless of their field of study. The volume covers everything from animal cognition to the state of current fisheries, from genetic modification to intersection animal activism. It is a rich resource for anyone interested in the moral issues that emerge from human interactions with animals"--
OCLC-licensed vendor bibliographic record.
Keywords: Animal welfare; Animal rights; Human-animal relationships; PHILOSOPHY / General